The armoured scale Oceanaspidiotus spinosus (Hemiptera: Diaspididae) established in New Zealand. Issue 1 (2nd January 2020) - Keall, John B.; Hartnett, Dominic E.; McCambridge, Josephine E.; Shaw, Nicola M.; Pearce, Brittany M.; Alkelov, Svea; Adoracion, Fely T.; Aliakbarpour, Hamaseh; Page, Graeme D.; Prasad, Pranish
ABSTRACT: The armoured scale insect Oceanaspidiotus spinosus (Comstock 1883) (Hemiptera: Diaspididae) was found on kiwifruit from the Bay of Plenty in April 2019. This is the first record from New Zealand. Subsequent surveys have confirmed O. spinosus at multiple locations in the Bay of Plenty and Gisborne regions and it is now considered to be established. Previously, only three armoured scale species: Hemiberlesia lataniae, Hemiberlesia rapax and Aspidiotus nerii, have been found on kiwifruit in New Zealand. Reliable identification of these species and O. spinosus requires slide mounting and microscopic examination of adult female specimens. Oceanaspidiotus spinosus is a cosmopolitan species recorded in 51 countries and island states. It is highly polyphagous and has been found on many host plants including kiwifruit, avocado, citrus, apple, persimmon, grape and blueberry. Although O. spinosus is not reported to be a major pest of these hosts, it may have market access implications for exported crops.